The Meetings of British and of American Economists - Carver, T. N. (Quarterly Journal of Economics, 1907)
The Meetings of British and of American Economists T. N. Carver T. N. Carver Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 22, Issue 1, November 1907, Pages 125–127, https://doi.org/10.2307/1883355 Published: 01 November 1907